2001
DOI: 10.1046/j.1442-2050.2001.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy followed by surgery for thoracic esophageal cancer potentially or actually involving adjacent organs

Abstract: The objective of this study was to evaluate the therapeutic usefulness of chemoradiotherapy (CRT) followed by surgery in patients with clinically T4 (cT4) esophageal cancer involving adjacent organs such as the trachea, main bronchi, and large vessels. Thirty-seven patients with cT4 squamous cell carcinoma of the thoracic esophagus were enrolled in this study. The CRT regimen comprised cisplatin (70 mg/m2) on day 1, 5-fluorouracil (700 mg/m2) on days 1-4 and external irradiation (200 cGy/day, total 30 Gy) on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 13 publications
2
41
0
4
Order By: Relevance
“…As shown in Tables 1 and Table 3, seven studies [10][11][12][13][14][15][16] have analyzed the outcome of patients with T4 esophageal cancer who underwent CRT-S. Basically, the combination of 5-FU (200-1000 mg/m 2 ) and CDDP (5-100 mg/m 2 ) was used in all the studies as the primary chemotherapeutic regimen. Although the doses of concurrent radiation varied across studies (36-60 Gy), all CRT in the series were performed as a "planned" treatment before surgical resection.…”
Section: Chemo-radiotherapy Followed By Surgery (Crt-s) Regimenmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Tables 1 and Table 3, seven studies [10][11][12][13][14][15][16] have analyzed the outcome of patients with T4 esophageal cancer who underwent CRT-S. Basically, the combination of 5-FU (200-1000 mg/m 2 ) and CDDP (5-100 mg/m 2 ) was used in all the studies as the primary chemotherapeutic regimen. Although the doses of concurrent radiation varied across studies (36-60 Gy), all CRT in the series were performed as a "planned" treatment before surgical resection.…”
Section: Chemo-radiotherapy Followed By Surgery (Crt-s) Regimenmentioning
confidence: 99%
“…Furthermore, 1 (2%) patient died of treatment-related cause (pancytopenia). Ikeda et al 15) reported that during and after CRT (60 Gy/5FU + CDDP), grade 3 toxicity included anemia (14% of patients) and leukocytopenia (14% of patients). In addition, 2 patients developed esophago-bronchial fistula, 2 esophago-vascular fistula, and 1 developed esophagomediastinal fistula.…”
Section: Chemo-radiotherapy Followed By Surgery (Crt-s) Regimenmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25] They reported that patients whose resected specimen showed complete response (CR) to neo-adjuvant chemoradiotherapy had the best survival. They frequently emphasized that minute residual tumors were often observed in the resected specimens, and that CR and minute residual tumors could not be defined only by pathological examinations of the resected specimen.…”
Section: The 3rd Stage Of Esophageal Surgery In Japanmentioning
confidence: 99%